Evaluating the effectiveness of development-limiting boundary control policy: Spatial difference-in-difference analysis. (September 2022) - Tan, Ronghui; Liu, Pengcheng; Zhou, Kehao; He, Qingsong
Abstract: Development-limiting boundaries are widely used in land use regulation in Chinese cities to curb urban sprawl and protect the ecosystem and environment. Land management law in China has recently required the delineation of urban development boundary in national-territory spatial planning of each city. However, limited studies have focused on whether these development-limiting boundaries effectively contain urban land growth in Chinese cities. Hence, effectiveness of these growth management policies remains unclear. This study investigates urban land growth inside and outside the ecological redline and uses spatial difference-in-difference models to evaluate the net effect of boundary on urban land growth in Wuhan. Results revealed that compared with their counterparts grandfathered under the ecological redline control policy, the average net increase of urban land growth inside the ecological redline is 2.2 % after the policy intervention, thereby suggesting that the Ecological Baseline Area regulation is not so useful but pro-growth policy in Urban Construction Area work in place. Inefficient coordination mechanism, technical limitations and the key role of local governments are responsible for the failure of the boundary control policy. Intensive reform on differentiated and urban–rural integrated land use policy design and public supervision mechanism construction is necessary in the future. Highlights: Spatial DID models are constructed to evaluate the effectiveness of development-limiting boundaries control policy. Development-limiting boundaries control policy failed to contain urban land growth. Urban land growth of a location is partially impacted by the growth of its nearby locations within the city.